Behantat: Warisan Budaya yang Menghidupkan Nilai dan Etika Sosial - Arviansyah, Muhammad Reza; Shagena, Ageng; Hudaidah, Hudaidah (Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This research focuses on the Behantat Tradition which is still preserved by the people of Sumber Rahayu Village, Rambang District, Muara Enim Regency, South Sumatra. Sumber Rahayu Village is one of the villages that still inherits and is strong in noble traditions and culture, although currently most traditions and culture are starting to be eroded by technological advances and globalization. So this research aims to find out the social values and ethics that develop and are contained in the behantat tradition. This type of research is qualitative research using methods including library research which is complemented by interviews to strengthen the data. The author collects information from various sources, such as books, articles, newspapers and relevant online media. Once the information is collected, the data is filtered to find the sources that best suit the research topic. The next step is to note down the important points and organize them into coherent writing that is relevant to the theme raised. The results of this research reveal that the stages of the behantat tradition consist of betandang (proposal), inter-antaran (behantat), mbalasi, and nari (party). There are social values and ethics, namely strengthening social harmony. Social values such as mutual cooperation, caring, and strengthening relationships are reflected in this tradition, where people work together and help each other in its implementation. Apart from that, social ethics such as mutual respect, politeness, responsibility, as well as simplicity and sincerity are also taught, making this tradition not only a cultural heritage, but also a guideline in social life.